Quantitative Analysis of Histidine Amino Acid as a Predictor of Ergothioneine in the Drying and Frying Process of White Oyster Mushrooms (Pleurotus ostreatus) - Dilla Dayanti; Windi Permatasari; Icha Khaerunnisa; Sri Winarni (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2021)
ABSTRACTBackgrounds: White oyster mushroom (Pleurotus ostreatus) is widely cultivated by Indonesian people due to its delicious and nutritious taste. Pleurotus ostreatus contains 18 amino acids that make up the body and antioxidants, including phenolic compounds and ergothioneine. Ergothioneine as a strong antioxidant is an amino acid derived from histidine which has sulfur groups such as cysteine and methionine. The increase in histidine indicates the activity of ergothioneine.Objectives: This study aims to determine the amino acid content of histidine as a predictor of ergothioneine amino acid in the drying and frying process of white oyster mushrooms.Methods: The extraction method used in this study was maceration with 90% ethanol for drying samples and 70% ethanol for frying samples analyzed using High Performance Liquid Chromatography (HPLC).Results: The results showed that the histidine content increased with the longer drying time, and decreased with the longer frying time. Drying with a variation of 2 days, 3 days, and 5 days were 674788,802 mg/L; 615302.747 mg/L; and 1946113,494 g / L respectively. Frying with a variation of 2 minutes, 3 minutes, and 5 minutes were 500435,148 mg / L; 232428,391 mg/L; and 0.000 mg / L. On the other hand, the methionine content decreased with the longer drying time, and increased with the longer frying time. Drying with a variation of 2 days, 3 days, and 5 days in a row were 6673,283mg/L; 6671,920 mg/L; and 1876,358 mg / L. Frying with a variation of 2 minutes, 3 minutes, and 5 minutes were 2296,698 mg / L; 1243,911 mg/L; and 34764.534 mg/L.Conclusions: the study concludes that the content of histidine as the highest ergothioneine predictor is at drying for 5 days and frying for 2 days.